(untitled) (Journal of the College of Basic Education, 2023)
The reason for choosing the topic is due to the strategic importance of the Red Sea region in global politics, as the Red Sea region witnessed an international race to gain a foothold in it, in addition to the intense American and Israeli naval presence in order to protect oil sources and supply routes. The research problem lies in the lack of official documents, and given For the geopolitical importance of the geostrategic and grand strategy of the Red Sea, whether in history, geopolitics, economy, war or strategy at the local, regional and international levels, we have prepared this research Given the nature of this historical study, the researcher was required to address the subject in an introduction, two chapters, an introduction, and a conclusion